2019
DOI: 10.1177/1179547619896577
|View full text |Cite
|
Sign up to set email alerts
|

Failed transcatheter pulmonary artery embolization in a patient suffering from massive hemoptysis after thoracic endovascular aortic repair

Abstract: An emergency thoracic endovascular aortic repair (TEVAR) with zone 2 landing without revascularization of the left subclavian artery was performed due to the impending rupture of a distal arch aneurysm in an old patient presenting hemoptysis. Two months later, the patient had recurrent massive hemoptyses and continued after additional zone 0 TEVAR. The lung parenchyma was considered to be the bleeding source and transcatheter pulmonary artery embolization was performed, and the episodes of massive hemoptysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…We agree with Anastasiadou et al 8 in that TEVAR should be the first therapy for all patients for hemodynamic stabilization, and could be the definite therapy in cases where an infectious factor is absent. However, our previous case 3 and the present case suggest that when additional TEVAR does not sufficiently treat post TEVAR hemoptysis, it is possible that ABF is not the main pathology; further endovascular repair would have no effect because the bleeding source is not the aorta but the adjacent lung parenchyma. In such cases, one should consider open aortic repair with resection of the diseased aorta and/or lung resection adjacent to the diseased aorta.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…We agree with Anastasiadou et al 8 in that TEVAR should be the first therapy for all patients for hemodynamic stabilization, and could be the definite therapy in cases where an infectious factor is absent. However, our previous case 3 and the present case suggest that when additional TEVAR does not sufficiently treat post TEVAR hemoptysis, it is possible that ABF is not the main pathology; further endovascular repair would have no effect because the bleeding source is not the aorta but the adjacent lung parenchyma. In such cases, one should consider open aortic repair with resection of the diseased aorta and/or lung resection adjacent to the diseased aorta.…”
Section: Discussioncontrasting
confidence: 55%
“…Where does bleeding come from in patients who underwent TEVAR? From our previous study 3 and the present experiences, we think there may be mixed pathologies cases that are commonly construed as ABF. Canaud et al 4 described postulated causes of ABF after TEVAR such as, stent graft coverage of the bronchial arteries leading to ischemic necrosis of the bronchial wall, chronic endoleaks leading to erosion into the adjacent lung, and penetration of the stent graft through the aortic wall into the lung.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…A previous study reported that the incidence of ABF after TEVAR was 0.6% (Czerny et al 2015a, b) and that endoleak is one of its major causes (Czerny et al 2015a, b;Karube et al 2019a, b;Sueyoshi et al 2018a, b). In addition to ABF, pulmonary artery pseudoaneurysm rupture associated with a mycotic TAA and chronic inflammatory reactions of the lung parenchyma secondary to the dispersion of atheroma and/or cholesterol embolization of the pulmonary vessel caused during a previous TAA rupture have been reported as etiologies of hemoptysis after the TAA repair Ishikawa et al 2019aIshikawa et al , b, 2020aMotohashi et al 2020a, b).…”
Section: Discussionmentioning
confidence: 99%
“…2015;Karube et al 2019;Sueyoshi et al 2018). On the other hand, hemoptysis in patients with TAA repair is known to occur other than ABF and pulmonary artery aneurysm rupture associated with a mycotic TAA(Ishikawa et al 2019), and the chronic in ammatory reaction of lung parenchyma secondary to dispersion of atheroma and/or cholesterol embolization of pulmonary vessels caused during a previous impending TAA rupture(Ishikawa et al 2020;Motohashi et al 2020) are reportedly its etiology.…”
mentioning
confidence: 99%